Parameters of Lexicographic Description of New Vocabulary of Modern German in Electronic Dictionary of Neologisms of Leibniz Institute for German Language - E. A. Smolonogina; I. O. Sitnikova (Научный диалог, 2022)
The problem of lexicographic fixation of neologisms at the present stage of development of German-language lexicography by private explanatory dictionaries of electronic format is considered. A fairly successful example of lexicographic practice was chosen as the object of the study — an electronic dictionary of neologisms of the modern German language on the lexicographic online portal of the Leibniz Institute for the German Language. The dictionary is a “living”, constantly updated edition, which is based on the criteria for the definition and classification of neologisms, developed by its compilers. The authors of the article performed an analysis of the parameters of the lexicographic description of neologisms in this dictionary. The question is raised about the mandatory or optional nature of the parameters used by the compilers of the dictionary when forming the microtext (dictionary entry). Standard and specific parameters of lexicographic description, which are profile for the dictionary of new words are distinguished: example-definition, first fixation, language reflection, encyclopedic information, representation in dictionaries, etc. The analysis of lexicographic practice sets the task of summarizing the practical experience of lexicographers in order to determine the optimal set of parameters for the codification of neology.